2022
DOI: 10.1002/adhm.202200998
|View full text |Cite
|
Sign up to set email alerts
|

Surface Bandgap Engineering of Nanostructured Implants for Rapid Photothermal Ion Therapy of Bone Defects

Abstract: Bone defects are seriously threatening the health of orthopedics patients and it is difficult for implants to accelerate bone regeneration without using bone growth factors. Herein, a fast photothermal ion therapeutic strategy is developed based on the bandgap engineering of nanostructured TiO 2 through (Si/P)-dual elemental doping by micro-arc oxidation treatment of titanium implants. The (Si/P)-dual doping can tune the surface bandgap structure of TiO 2 by decreasing bandgap and broadening valence band simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…After the micro-arc oxidation treatment, the titanium alloy gains a surface with a rich porous structure [ 38 , 39 ]. As the atomic force microscope showed, the surface roughness of the MAO substrate increases significantly, which creates a structural basis for the electrophoretic loading of iodine and the combination of the PCL coating in the later stage [ 40 , 41 , 42 ]. The tubular titanium dioxide structure on the surface of the titanium alloy, such as a pipe, can be loaded with iodine by electrophoresis, thereby ensuring enough content and long-term release ability of iodine [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the micro-arc oxidation treatment, the titanium alloy gains a surface with a rich porous structure [ 38 , 39 ]. As the atomic force microscope showed, the surface roughness of the MAO substrate increases significantly, which creates a structural basis for the electrophoretic loading of iodine and the combination of the PCL coating in the later stage [ 40 , 41 , 42 ]. The tubular titanium dioxide structure on the surface of the titanium alloy, such as a pipe, can be loaded with iodine by electrophoresis, thereby ensuring enough content and long-term release ability of iodine [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a visible-light absorption capability . From then on, doping has been extensively employed for TiO 2 with either non-metal anions of C, N, S, and P at the O sites or transition metal cations of Fe, Co, Cu, Cr, and Ni at the Ti sites. ,− …”
Section: Recent Developments Of Photothermal Nanomaterialsmentioning
confidence: 99%
“…Under UV or visible light illumination for 20 minutes, negative or positive charges were accumulated on the Gr/TN film respectively, which changed the conformation of extracellular matrix (ECM) molecules to a more disordered state, ultimately resulting in cell detachment. 68 However, limited studies on the in situ UV light-responsive strategy were little more than in vitro cell (1) Photocatalysis producing ROS (PDT) (1) PDT and/or PTT for antibacterial or anti-tumor applications 23,26,30,[39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]66,69 (2) Incorporating photosensitive molecules (PDA, RP, IR780 and etc.) 23,30,39, (2) Photo-triggered hyperthermia (PTT)…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
“…23,38,45,49 In particular, elemental doping can also enhance the photothermal activity of TiO 2 under NIR irradiation, and endow titanium implants with PDT and PTT effects simultaneously. [39][40][41]44,46,64 For example, Zhang et al 41 reported a multifunctional NIR light-triggered antibacterial coating on titanium implants for reconstructing osteosarcoma-related bone defects. In this study, the authors fabricated a phototherapy platform based on up-conversion elements (Yb and Er)-doped TiO 2 nano-shovels (TiO 2 @UNC) through a two-step hydrothermal treatment, which were subsequently covalently immobilized with quercetin (Qr, a flavonoid compound with multiple therapeutic effects) and then electrostatically integrated with L-arginine (LA).…”
Section: Enzymesmentioning
confidence: 99%